Changing feedbacks in the climate–biosphere system. Issue 6 (1st August 2008) - Chapin, F Stuart; Randerson, James T; McGuire, A David; Foley, Jonathan A; Field, Christopher B
Abstract : Ecosystems influence climate through multiple pathways, primarily by changing the energy, water, and greenhouse‐gas balance of the atmosphere. Consequently, efforts to mitigate climate change through modification of one pathway, as with carbon in the Kyoto Protocol, only partially address the issue of ecosystem–climate interactions. For example, the cooling of climate that results from carbon sequestration by plants may be partially offset by reduced land albedo, which increases solar energy absorption and warms the climate. The relative importance of these effects varies with spatial scale and latitude. We suggest that consideration of multiple interactions and feedbacks could lead to novel, potentially useful climate‐mitigation strategies, including greenhouse‐gas reductions primarily in industrialized nations, reduced desertification in arid zones, and reduced deforestation in the tropics. Each of these strategies has additional ecological and societal benefits. Assessing the effectiveness of these strategies requires a more quantitative understanding of the interactions among feedback processes, their consequences at local and global scales, and the teleconnections that link changes occurring in different regions.